Fulfilling the PEPFAR mandate: a more equitable use of PEPFAR resources across global health - Barbiero, Victor K (Global Health: Science and Practice, 2013)
As PEPFAR moves beyond its “emergency stage,” it should now help support a more sustainable development mode, including an equitable platform for meeting a broad range of priority health needs, while continuing to pursue the goal of an AIDS-free generation.